1978
DOI: 10.1104/pp.61.3.365
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Aging in Soybean Seeds

Abstract: Changes in seeds of soybeans (Glycine max IL.I Meff. var. Wayne) which occur during accelerated aging (41 C, 100% relative humidity) showed subsequent loss of vigor, a decline in early respiratory activity, increased leakage of electrolytes, losses of as much as 10% dry weight from imbibing cotyledons, and a decrease in the swelling response of the imbibing system (seed plus H20). Each of these changes with aging is interpreted as resulting from deteriorative changes in membranes.The performance capability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
75
0
5

Year Published

1979
1979
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(88 citation statements)
references
References 19 publications
8
75
0
5
Order By: Relevance
“…Most frequently this acceleration has been accomplished through storage of seeds at high temperatures and humidities (typically 40-450C and 100%1o RH) (7,(14)(15)(16)(17)(18). Such techniques may introduce damage processes not present in naturally aging seeds and/ or alter the relative rates of damage processes responsible for aging.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most frequently this acceleration has been accomplished through storage of seeds at high temperatures and humidities (typically 40-450C and 100%1o RH) (7,(14)(15)(16)(17)(18). Such techniques may introduce damage processes not present in naturally aging seeds and/ or alter the relative rates of damage processes responsible for aging.…”
Section: Resultsmentioning
confidence: 99%
“…Oxygen Aging Block' (Scott Testers, Inc., Providence, RI). High purity oxygen and nitrogen were obtained from Matheson (East Rutherford, NJ) and used without further purification.In experiments designed to approximate published procedures for accelerated aging (1,14,15,17,18) …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The initial time course of solute leakage from the imbibing cotyledon also shows a period of rapid, nonlinear leakage, followed by a linear phase beginning at about the same time that water entry becomes linear. It has been suggested that the initial rapid phases of each of these events represented a period during which the membranes were relatively disorganized, and the linear phases represented steady-state processes through the reorganized membranes (7,8,11 (6.7-8 mm). Some cotyledons were heatkilled at 100 C overnight.…”
Section: Resultsmentioning
confidence: 99%
“…Alterations in the membranes of aged seeds are considered to lead to a greatly enhanced leakage of solutes during seed imbibition (2,13). This may be indicative of an inability to re-form coherent membranes during rehydration of the seed, resulting in loss of vigor and lack of germination.…”
mentioning
confidence: 99%